Hábitos alimentarios que afectan a pacientes con diabetes mellitus del Centro de Salud Guanujo del Cantón Guaranda. Periodo octubre 2024 - mayo 2025. - Vergara Navarrete, Jazmín Elizabeth (2025)
Diabetes mellitus is a chronic metabolic disease whose control requires a comprehensive approach, including monitoring, medication administration, and especially the adoption of appropriate eating habits. These habits can directly influence the stability of glucose levels and the prevention of long-term complications. Objective: To determine the influence of eating habits on diabetes control in patients attending the Guanujo Health Center in Guaranda Canton. Methodology: This was a field-based, non-experimental, analytical, correlational, cross-sectional study with a quantitative approach using deductive, inductive, and analytical methods. It was based on bibliographic theories, data collection through a survey validated by experts, and fasting glucose levels. Results: The largest proportion of adults studied was female, at 64.9%, while males accounted for 35.1%. The highest age group was adults over 65 years of age, at 47.4%, followed by 38.6% between 50 and 64 years of age, and the lowest age group was those between 25 and 49 years of age, at 14%. It was observed that the adults had poor eating habits, with a low consumption of foods with a low or moderate glycemic index and a high consumption of foods with a glycemic index greater than 70, such as white bread, rice, and processed foods. Control was assessed, and it was observed that 50.88% of adults had elevated glucose levels, thus demonstrating a relationship between the two variables studied, with a p value of <0.05.